Career Opportunities For Students Of Mandarin Language Education Study Program In Tourism Industry - Ramadhani, Aulia Putri; Karina Fefi Laksana Sakti; Deddy Kurniawan (Nexus Publishing NXP, 2025)
Tourism is a strategic sector that contributes significantly to global economic growth. In Indonesia, this sector serves as one of the main pillars of national economic development, particularly with the increasing number of international tourists—including those from China—visiting various destinations such as Malang City. This phenomenon opens up new opportunities in the job market, especially for graduates of the Mandarin Language Education Study Program. This study aims to identify the career potential of students in this program within the tourism industry. Using a descriptive qualitative approach, data were collected through questionnaires distributed to students and tourism industry practitioners. The analysis results show that most students express a strong interest in pursuing careers in this sector. The most in-demand and popular profession is that of a tour guide, especially those who are able to communicate in Mandarin. Nevertheless, the main challenge faced is the lack of practical foreign language proficiency and other supporting skills. Therefore, it is necessary to improve competencies through language training and professional skill development so that graduates are better prepared to compete in the job market, particularly in the tourism sector, which is based on service and cross-cultural communication.